Bank complexity, governance, and risk - Correa, Ricardo; Goldberg, Linda S. (Journal of Banking & Finance, 2022)
Bank holding companies (BHCs) can be complex organizations, conducting multiple lines of business through many distinct legal entities and across a range of geographies. While such complexity raises the costs of bank resolution when organizations fail, the effect of complexity on BHCs’ broader risk profiles is less well understood. Business, geographic, and organizational complexity can engender explicit tradeoffs between the agency problems that increase risk and the diversification, liquidity management, and synergy improvements that reduce risk. The balance of outcomes may depend on the strength of bank governance. We test these conjectures using data on large U.S. BHCs for the 1996–2018 period. Business, geographic, and organizational complexity provide diversification benefits and some reduced idiosyncratic and liquidity risk exposure. All forms of complexity tend to increase BHC systemic risks. A regulatory tightening focused on complexity reduced organizational complexity, while also curtailing systemic risk but increasing liquidity risk.